BS EN IEC 61753-021-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 021- 02. Single-mode fibre optic connectors terminated as pigtails and patchcords for category C. Controlled environment (23rd July 2021) - British Standards Institution,
No abstract available